The effectiveness of the Youth-Oriented Mental Health Education Program (Y-MIND) school-based psychoeducational program in improving mental health literacy and reducing psychological distress among adolescents in Klaten, Indonesia: A quasi-experimental study - Astri Wahyuningsih; Lusiana Ambarsari; Leni Prasetiyani; Indah Yunita Khairunisa (Lentera Perawat, 2026)
Background: Adolescent mental health is a major public health concern, including in Indonesia, where many cases remain undetected and untreated. Limited mental health literacy may contribute to poor help-seeking behavior and adverse mental health outcomes. Psychoeducation is a promising school-based strategy to address these challenges. Objective: This study aimed to evaluate the effectiveness of the Youth-Oriented Mental Health Education Program (Y-MIND) in improving mental health literacy and reducing psychological distress among adolescents. Methods: A quasi-experimental pretest–posttest control group design was conducted among 70 eleventh-grade students at SMA Muhammadiyah 1 Klaten, Indonesia. Participants were selected using proportional stratified random sampling and assigned to an intervention group (n = 35) and a control group (n = 35). The intervention group received the four-session Y-MIND psychoeducational program. Mental health status was assessed using the Self-Reporting Questionnaire-20 (SRQ-20), and mental health literacy was measured using the Multicomponent Mental Health Literacy Measure (MMHLM). Data were analyzed using the Wilcoxon signed-rank test and Mann–Whitney U test. Results: The proportion of participants without psychological distress increased from 45.7% to 91.4% in the intervention group, compared with 60.0% to 62.9% in the control group. High mental health literacy increased from 5.7% to 74.3% in the intervention group. Between-group analysis showed significantly greater improvements in psychological distress (p = 0.001) and mental health literacy (p < 0.001) in the intervention group compared with the control group. Conclusion: The Y-MIND program effectively improved mental health literacy and reduced psychological distress among adolescents. School-based psychoeducation may be an effective strategy for promoting adolescent mental health.